Osservazioni sulle correlative in vedico (Atti del Sodalizio Glottologico Milanese, 2014)
The study of the structure of correlative sentences is of great importance in the context of Indo-European syntax, since this strategy of relativization is present in all earliest attested Indo-European languages, or, at least in the archaic phases of some of them. Interestingly, the model of external-headed relative clauses is present today in Hindi, but it seems not to have ever developed in Vedic (nor in Hittite), in which any expression of (explicit) relative clauses must make use of the correlative  construction. KEYWORDS: Vedic syntax, correlative clauses, Indo-European syntax, Indo-European relative clauses, hyperbaton